Biophysical and biochemical markers at 30–34 weeks' gestation in the prediction of adverse perinatal outcome. (7th January 2016) - Valiño, N.; Giunta, G.; Gallo, D. M.; Akolekar, R.; Nicolaides, K. H.
ABSTRACT: Objective: To investigate the potential value of biophysical and biochemical markers at 30–34 weeks' gestation in the prediction of adverse perinatal outcome. Methods: This was a screening study in 8268 singleton pregnancies at 30–34 weeks' gestation. Estimated fetal weight (EFW), uterine artery (UtA) pulsatility index (PI), umbilical artery (UA) PI, fetal middle cerebral artery (MCA) PI, mean arterial pressure (MAP), serum placental growth factor (PlGF) and soluble fms‐like tyrosine kinase‐1 (sFlt‐1) were measured. The detection rate (DR) and false‐positive rate (FPR) of screening by each biomarker were estimated for stillbirth, pre‐eclampsia, delivery of small‐for‐gestational‐age (SGA) neonate, Cesarean section for fetal distress before or during labor, umbilical arterial cord blood pH ≤7.0 or umbilical venous cord blood pH ≤7.1, 5‐min Apgar score < 7 and admission to the neonatal unit (NNU). Results: Multivariable regression analysis demonstrated that significant prediction of PE was provided by PlGF, sFlt‐1, MAP and MCA‐PI, with a DR of 98% for PE delivering < 37 weeks' gestation and 56% for those delivering ≥ 37 weeks, at a 10% FPR. Prediction of SGA was provided by EFW, PlGF, sFlt‐1, UtA‐PI, UA‐PI and MCA‐PI, with a DR of 88% for SGA delivering < 37 and 51% for those delivering ≥ 37 weeks' gestation, at a 10% FPR. Prediction of stillbirth was provided by EFW, UtA‐PI and MCA‐PI, with DR of 30% at 10% FPR. Prediction of Cesarean section for fetal distress before labor was provided by EFW, sFlt‐1, UtA‐PI and UA‐PI, with a DR of 90% at a 10% FPR. Prediction of fetal distress in labor was provided by EFW and sFlt‐1, with a DR of 16% at a 10% FPR. There were no significant differences from the normal outcome group in any of the biomarkers for low cord blood pH, low Apgar score or NNU admission for cases other than those with PE and/or SGA. Conclusion: At 30–34 weeks' gestation, biomarkers of impaired placentation and fetal hypoxemia provide good prediction of PE, SGA and fetal distress before labor, but poor or no prediction of stillbirth and adverse events in labor or after birth. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.